Implementasi Metode Qiyasi dalam Pembelajaran Nahwu Kelas XI Ma Ibnu Qoyyim Putra Yogyakarta - Aisyam Mardliyyah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
This article aims to describe the implementation of Nahwu learning by using the Qiyasi method in XI grade class of MA Ibnu Qoyyim Putra as well as students' responses regarding the Qiyasi method in nahwu learning. The method used in this research is a qualitative research with field research, the research subjects used are the students of XI grade, amounting to 42. While the data collection technique is observation, interviews and documentation. Then the data analysis technique is descriptive analysis. The data obtained are sourced from nahwu teachers, XI grade students and other parties concerned. The result in this research shows that the Qiyasi method is suitable for the intermediate level because this method is practical and understanable for recognizing â€œNahwuâ€ but this method also has to be supported by the interaction of teachers and active students. Factors that influence learning are the enthusiasm of the teacher and his motivation in conveying. The inhibiting factor is inadequate facilities, especially the absence of an education manual and only relies on material from teachers.